2022
DOI: 10.1186/s12890-022-01858-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between peak inspiratory flow and hand grip strength measurement in men with mild chronic obstructive pulmonary disease

Abstract: Background Chronic obstructive pulmonary disease (COPD) decreases quality of life and muscular strength. Inspiratory flow is important for inhalants in the bronchi but is complicated to measure in routine practice. We hypothesized that hand grip strength (HGS) would correlate with inhalation rate in patients with mild COPD. Methods The COPD patients were recruited at the St. Marianna University School of Medicine, Yokohama Seibu Hospital, from 2015… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…This study differed from our study in that the investigators did not derive a prediction equation for PIFR considering both genders and all stages of disease, and they did not identify a HGS cutoff value associated with suboptimal PIFR. Our study showed higher correlation coefficients of HGS and PIFR (r = 0.591 for Accuhaler and r = 0.614 for Turbuhaler) than the study by Tsuburai [ 21 ], probably because of the larger number of patients in our study and the broader range of HGS. A study of 75 hospitalized patients with acute exacerbation of COPD by Samarghandi et al [ 3 ] demonstrated that HGS was significantly correlated with Accuhaler PIFR.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This study differed from our study in that the investigators did not derive a prediction equation for PIFR considering both genders and all stages of disease, and they did not identify a HGS cutoff value associated with suboptimal PIFR. Our study showed higher correlation coefficients of HGS and PIFR (r = 0.591 for Accuhaler and r = 0.614 for Turbuhaler) than the study by Tsuburai [ 21 ], probably because of the larger number of patients in our study and the broader range of HGS. A study of 75 hospitalized patients with acute exacerbation of COPD by Samarghandi et al [ 3 ] demonstrated that HGS was significantly correlated with Accuhaler PIFR.…”
Section: Discussioncontrasting
confidence: 82%
“…A previous study of 44 clinically stable patients with COPD by Tsuburai et al [ 21 ] showed a significant positive correlation between HGS and PIFR for Accuhaler (r = 0.326, p = 0.031) and Turbuhaler (r = 0.328, p = 0.030). This study differed from our study in that the investigators did not derive a prediction equation for PIFR considering both genders and all stages of disease, and they did not identify a HGS cutoff value associated with suboptimal PIFR.…”
Section: Discussionmentioning
confidence: 88%
“…Knowledge (knowledge and learning) is the foundation, belief (belief and attitude) is the motivation, and action (promoting healthy behavior) is the goal. COPD patients have a long course of disease and repeated attacks of disease, which brings a heavy economic burden to the family and society [ 42 ]. Nurse-led health education based on knowledge, belief, and practice is a scientific nursing method.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to have excellent reproducibility and a good correlation with PIF derived from spirometry [39, 42, 43, 45] and is increasingly recognized as an easy and fast way to evaluate PIF [4649]. Different studies show a good correlation between low handgrip strength and weak PIF, which may serve as a surrogate to estimate PIF [23, 5053]. For example, Frohnhofen et al [50] demonstrated this correlation, with a positive predictive value of 79% and a negative predictive value of 84%.…”
Section: Resultsmentioning
confidence: 99%